Crisis communication and public trust: insights from social media use in Kazakhstan - Burkitbayeva, M. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The study presents the results of a quantitative investigation into the behavior of the public in Kazakhstan during a crisis. Two hundred two participants were surveyed as part of the study to determine what elements affect the public’s opinion of an organisation’s crisis response and what influences the public’s trust in organisations during a crisis. Survey data were analysed to ascertain how the public’s use of social media influences their opinion of an organisation’s response to a crisis and the elements that affect public trust in organisations during a crisis. The study’s conclusions significantly impact organizations hoping to foster public trust and successfully convey their crisis responses. This study is critical because it sheds light on how the Kazakhstani populace behaves during a crisis. The findings can assist organizations in communicating their responses to the public and fostering public trust during a crisis. Additionally, the study offers insightful data regarding how the public uses social media in times of crisis, which can assist companies in adjusting their communication plans to reach the audience better.